Prevention of Gestational Diabetes: Design of a Cluster-Randomized Controlled Trial and One-Year Follow-Up - Mansikkamäki Kirsi; Ojala Katriina; Aittasalo Minna; Kinnunen Tarja I; Luoto Riitta M; Toropainen Erja; Kolu Päivi; Vasankari Tommi (BMC, 2010)
Abstract Background Annual prevalence of gestational diabetes mellitus (GDM) is 12.5% among Finnish pregnant women. The prevalence is expected to rise with the increasing overweight among women before pregnancy. Physical activity and diet are both known to have favourable effects on insulin resistance and possibly on the risk of GDM. We aimed to investigate, whether GDM can be prevented by counseling on diet, physical activity and gestational weight gain during pregnancy. Methods/Design A cluster-randomized controlled trial was conducted in 14 municipalities in the southern part of Finland. Pairwise randomization was performed in order to take into account socioeconomic differences. Recruited women were at 8-12 weeks' gestation and fulfilled at least one of the following criteria: body mass index ≥ 25 kg/m2, history of earlier gestational glucose intolerance or macrosomic newborn (> 4500 g), age ≥ 40 years, first or second degree relative with history of type 1 or 2 diabetes. Main exclusion criterion was pathological oral glucose tolerance test (OGTT) at 8-12 weeks' gestation. The trial included one counseling session on physical activity at 8-12 weeks' gestation and one for diet at 16-18 weeks' gestation, and three to four booster sessions during other routine visits. In the control clinics women received usual care. Information on height, weight gain and other gestational factors was obtained from maternity cards. Physical activity, dietary intake and quality of life were followed by questionnaires during pregnancy and at 1-year postpartum. Blood samples for lipid status, hormones, insulin and OGTT were taken at 8-12 and 26-28 weeks' gestation and 1 year postpartum. Workability and return to work were elicited by a questionnaire at 1- year postpartum. Linkage to the national birth register of years 2007-2009 will provide information on perinatal complications and GDM incidence among the non-participants of the study. Cost-effectiveness evaluation will be based on quality-adjusted life years. This study has received ethical approval from the Ethical board of Pirkanmaa Hospital District. Discussion The study will provide information on the effectiveness and cost-effectiveness of gestational physical activity and dietary counseling on prevention of GDM in a risk group of women. Also information on the prevalence of GDM and postpartum metabolic syndrome will be gained. Results on maintaining the possible health behaviour changes are important in order to prevent chronic diseases such as cardiovascular disease and diabetes. Trial registration The trial is registered ISRCTN 33885819